An isotopic test of the seasonal migration hypothesis for large grazing ungulates inhabiting the Palaeo-Agulhas Plain. (1st May 2020) - Hodgkins, Jamie; Marean, Curtis W.; Venter, Jan A.; Richardson, Leesha; Roberts, Patrick; Zech, Jana; Difford, Mark; Copeland, Sandi R.; Orr, Caley M.; Keller, Hannah May; Fahey, B. Patrick; Lee-Thorp, Julia A.
Abstract: The Greater Cape Floristic Region of South Africa was critical to the evolution of early modern humans ( Homo sapiens ) during the Pleistocene. The now submerged continental shelf formed its own ecosystem, the Palaeo-Agulhas Plain (PAP), where early humans lived and foraged. Grazing animals living on the plain might have migrated east and west tracking seasonally varying rains—a hypothesis tested here by examining δ 13 C and δ 18 O of serially-drilled teeth from seven ungulate genera: Alcelaphus, Connochaetes, Antidorcus, Redunca, Damaliscus, and Hippotragus . Modern observations and paleoecological reconstructions indicate that summer rainfall areas to the east have more C4 grasses while the winter rainfall areas to the west have more C3 grasses, and that summer and winter rains differ in δ 18 O. Thus, we analyze δ 13 C and δ 18 O preserved in herbivore teeth from the site of PP30 (a hyena den dating to ∼151 ka) to infer diet and water source throughout tooth formation. On a generic level, none of the samples exhibit δ 13 C or δ 18 O values that differ significantly from a taxon that likely foraged locally through the year (Southern reedbuck, Redunca arundium ). Overall, results indicate that the PAP could support herbivore populations year-round without substantial migration, providing an ecosystem ideal for human inhabitants. Highlights: The now submerged South African continental shelf once formed its own ecosystem, the Palaeo-Agulhas Plain (PAP) where humans lived and foraged. This area of South Africa is home to some of the earliest clearly human associated occupations anywhere in Africa. δ 13 C and δ 18 O of serially-drilled teeth from herbivores show the PAP could support herbivore populations year-round. The PAP provided an ecologically rich ecosystem ideal for human inhabitants, and human evolution.